Synergistic effects produced by certain antioxidants in valuable functional foods from the Romanian markets - Savescu, Petre; Tita, Ovidiu; Poenaru, Maria Magdalena; Nistor, Catalin (Frontiers in Nutrition, 2025)
Today, people should change their lifestyles and nutrition to prevent metabolic diseases characteristic of our century. Functional foods, rich in antioxidants, greatly help combat everyday stress and ensure optimal nutritional density. This study is part of an applied research and experimental development program for valuable functional foods that are promoted in the Romanian market. In this research—conducted from 2020 to the present at the INCESA Institute for Applied Science Research at the University of Craiova, Romania—the occurrence and optimization of redox processes and synergistic effects in organic carrot juices were tested. These effects arise from the interaction between certain antioxidants (beta-carotene, lycopene, vitamin A) in raw organic juice and the food additives used in manufacturing recipes. Optical analysis methods (UV–Vis molecular absorption spectroscopy and atomic absorption spectroscopy) were used to monitor the technological processes, while supercritical fluid extraction with activated bio-membranes and combined field induction technology (plasmatic, magnetic, gravitational) were used to optimize certain operations and activate valuable biocomponents. The study confirmed the research hypothesis that the proposed new activation technology optimized the reaction mechanisms and synergistic and antagonistic effects occurring in the processing of organic carrots. This resulted in new functional food variants that are much richer in valuable activated bio-compounds and compositionally stable during long-term storage. Furthermore, the application of new technologies and the optimization of synergistic effects led to the development of protective mechanisms against Escherichia coli-type microorganisms in the final juice products. The study provides novel and valuable insights into the design and development of organic juices with optimized nutritional density (functional foods). This is extremely important for consumers and the shelf life of the product.